The effect of protein intake on athletic performance: a systematic review and meta-analysis - Zhao, Shiao; Zhang, Hong; Xu, Yipin; Li, Jiarui; Du, Senyao; Ning, Ziheng (Frontiers in Nutrition, 2024)
The impact of a protein-rich diet and protein supplements on athletes' performance remains a topic of debate. Does protein intake confer benefits for athletes? Methods: This study aimed to explore the relationship between protein intake and athletic performance. A systematic database search was conducted to identify randomized controlled trials examining the effects of protein intake on athletes' performance. The databases searched included PubMed, Scopus, Web of Science, EBSCO, and Ovid. The meta-analysis included a total of 28 studies involving 373 athletes. The meta-analysis employed both the fixed-effects model and the random-effects model to investigate the impact of protein intake on sports performance. Subgroup analysis aimed to provide solid evidence to explain the results of the meta-analysis. Sensitive analysis and funnel plots were used to detect the risk of bias and the robustness of data.Results: Overall, the protein group did not show a statistically significant improvement in athletic performance (standardized mean difference [SMD] = 0.12, 95% confidence interval [CI]: -0.01 to 0.25). However, in subgroup analysis, the protein group demonstrated a statistically significant improvement in endurance performance, as indicated by the forest plot of final value (SMD = 0.17, 95% CI: 0.02 to 0.32). Additionally, the change value in the forest plot for endurance performance showed greater statistical significance compared to the final value (SMD = 0.31, 95% CI: 0.15 to 0.46). In the subgroup analysis based on types of physiological indices, muscle glycogen showed a statistically significant improvement in the protein group (standardized mean difference [SMD] = 0.74, 95% confidence interval [CI]: THE EFFECT OF PROTEIN INTAKE ON ATHLETIC PERFORMANCE 0.02 to 0.32). In the subgroup analysis based on types of protein supplementation strategy, the protein plus carbohydrate group demonstrated statistically significant improvements in endurance performance (SMD = 0.36, 95% CI: 0.11 to 0.61), whereas the high protein group did not.In conclusion, protein intake appears to offer slight benefits to athletic performance, particularly in enhancing endurance. The subgroup analysis suggests that muscle glycogen levels improved with protein intake, and that co-ingestion of protein and carbohydrates is more effective than high protein intake alone in endurance athletes.PROSPERO registration number: (CRD42024508021).